Mubadalah-Based Personality Development Programs for Inmates in Preventing Crime and Marital Dissolution in Lampung Correctional Institutions - Muhammad Zuhri; Wahyu Abdul Jafar; Refly Setiawan; Anggalana (Universitas Islam Negeri Raden Intan Lampung, 2025)
The The high levels of recidivism and marital dissolution among inmates’ families indicate that personality development programs within correctional institutions have not yet adequately supported social reintegration and family resilience. Accordingly, this study examines the effectiveness of inmate personality development programs in preventing recidivism and divorce, as well as their contribution to the development of family law grounded in the mubadalah perspective. This research constitutes a field study employing a qualitative approach conducted in three correctional institutions in Lampung Province. Data were collected through in-depth interviews, observation, and document analysis involving six key informants consisting of correctional officers and inmates. The data were analyzed through data reduction, thematic coding, and source triangulation, with mubadalah theory serving as the primary analytical framework. The findings indicate that religion-based personality development programs contribute positively to changes in inmates’ attitudes and moral awareness; however, they have not yet proven effective in significantly reducing recidivism (562 cases) and marital dissolution (21 cases). This study recommends strengthening reciprocity-based religious development programs, fostering collaboration with higher religious organizations, and integrating mubadalah values into correctional policies.